Zeichen/Momente. Vergegenwärtigungen in Kunst und Kulturanalyse - Adorf, Sigrid; Heinz, Kathrin (transcript, 2019)
Artistic, cultural and social practices are spaces where complex structure of meaning and relationships are negotiated - this book illuminates versatile discourse stories at the interfaces of aesthetics, cultural and media studies.